New inequalities using fractional q-integrals theory - DAHMANI, ZOUBIR; BENZIDANE, ABDELKADER (Bulletin of Mathematical Analysis and Applications, 2012)
The aim of the present paper is to establish some new fractional q-integral inequalities on the speci c time scale: T t 0 = { t : t = t 0 q n ;n ∈ N }∪{ 0 } ; where t 0 ∈ R; and 0 <q< 1.
Keywords: Fractional q -calculus, q -Integral inequalities.